Effects of foot rotation on ACL injury risk variables during drop landing - Peel, S. A.; Thorsen, T. A.; Schneider, L. G.; Weinhandl, J. T. (Journal of Science in Sport and Exercise, 2020)
Purpose: Landing is considered a "high-risk" movement for anterior cruciate ligament (ACL) injuries. Foot progression angle (FPA) during landing has been shown to influence hip, knee, and ankle mechanics. The purpose of this study was to compare five FPA conditions during drop landings between males and females. Methods: Twenty males and females were tested using five FPA conditions: self-selected, toe-in 15°, toe-in 30°, toe-out 15°, and toe-out 30°. Right hip, knee, and ankle joint kinematics and kinetics were collected using a 12-camera motion capture system and two force plates. Five successful trials were collected and compared between FPA conditions. Results: The main effect for FPA condition was statistically different for initial contact hip flexion, hip abduction, hip internal rotation, knee flexion, knee abduction, knee external rotation, and ankle inversion angles compared to self-selected FPA at P < 0.05. Peak hip extension, hip abduction, knee adduction, knee internal rotation, ankle plantar flexion, and ankle inversion moments were also found to be statistically significant (P < 0.05). Overall, females experienced greater initial knee abduction angle (P = 0.028), hip abduction moment (P = 0.006), knee extension moment (P = 0.033), and knee internal rotation moment (P = 0.044), regardless of FPA condition. Males experienced greater initial contact hip abduction angle (P = 0.0017), regardless of FPA condition. Conclusion: The results suggest that landing with large toe-in FPA will increase the magnitude of ACL injury risk variables, and females demonstrated a greater magnitude in these variables compared to males. Injury prevention programs may seek to target FPA as part of training activities to avoid large FPA toe-in landings.